1998
DOI: 10.1677/joe.0.1590403
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes expressed in the rat prostate that are modulated differently by castration and Finasteride treatment

Abstract: In mammals, testosterone and 5 -dihydrotestosterone (DHT) are the principal male hormones (androgens). Testosterone is the most abundant circulating androgen, and is converted in specific tissues to DHT by the 5 -reductase enzymes. Although each of these androgens binds to the same receptor protein (androgen receptor, AR), each exerts biologically distinct effects. Theories to explain the specific effects of testosterone and DHT have centered on kinetic differences of binding of androgens to the receptor or di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 19 publications
1
16
0
1
Order By: Relevance
“…This is supported by crystallographic studies showing nearly identical interactions of T and DHT with the AR ligand-binding pocket (15). However, the effects of T and DHT on gene expression are not always equivalent, as they differentially regulate the expression of a subset of AR target genes in the prostate (38)(39)(40) and the ovaries (5,15,20,41). The mechanisms of the differential response of ovarian granulosa cells to T or DHT have not been previously examined.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by crystallographic studies showing nearly identical interactions of T and DHT with the AR ligand-binding pocket (15). However, the effects of T and DHT on gene expression are not always equivalent, as they differentially regulate the expression of a subset of AR target genes in the prostate (38)(39)(40) and the ovaries (5,15,20,41). The mechanisms of the differential response of ovarian granulosa cells to T or DHT have not been previously examined.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, DHT had no significant effect on either WHR or triacylglycerol uptake . Differential display PCR has already shown that testosterone and DHT have different effects on prostate gene expression (Avila et al 1998). The different and sometimes opposite actions of testosterone and DHT may indicate that testosterone effects are mediated by a compound created via the aromatization process (Jensen 2000).…”
Section: Figurementioning
confidence: 99%
“…Although 5α-dihydrotestosterone (5α-DHT) is the most important androgen in tetrapod males (Avila et al, 1998), in teleost fish the 11-oxygenated androgens are considered as the more potent androgenic steroids (Borg, 1994;Kime, 1993;Lokman et al, 2002), and the general assumption has been that 5α-DHT had no major physiological role in this vertebrate group (Borg, 1994;Cavaco et al, 1998) until Margiotta-Casaluci et al (2013a reported high plasma levels in adult fathead minnow, Pimephales promelas. In the same species, exposure to 200 ng/L of 5α-DHT showed an in vivo androgenic potency comparable to 11-ketotestosterone (11-KT).…”
Section: Introductionmentioning
confidence: 99%